Application of CRISPR/Cas Genomic Editing Tools for HIV Therapy: Toward Precise Modifications and Multilevel Protection - Maslennikova, Alexandra; Mazurov, Dmitriy (Frontiers in Cellular and Infection Microbiology, 2022)
Although highly active antiretroviral therapy (HAART) can robustly control human immunodeficiency virus (HIV) infection, the existence of latent HIV in a form of proviral DNA integrated into the host genome makes the virus insensitive to HAART. This requires patients to adhere to HAART for a lifetime, often leading to drug toxicity or viral resistance to therapy. Current genome-editing technologies offer different strategies to reduce the latent HIV reservoir in the body. In this review, we systematize the research on CRISPR/Cas-based anti-HIV therapeutic methods, discuss problems related to viral escape and gene editing, and try to focus on the technologies that effectively and precisely introduce genetic modifications and confer strong resistance to HIV infection. Particularly, knock-in (KI) approaches, such as mature B cells engineered to produce broadly neutralizing antibodies, T cells expressing fusion inhibitory peptides in the context of inactivated viral coreceptors, or provirus excision using base editors, look very promising. Current and future advancements in the precision of CRISPR/Cas editing and its delivery will help extend its applicability to clinical HIV therapy.